Дисперсионные свойства геликонов в периодической полупроводниковой структуре - Булгаков, А.А.; Ольховский, Е.А.; Шрамкова, О.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The band spectrum of a semiconductor periodic structure is investigated. It is supposed that the structure is placed into an external magnetic field parallel to the boundaries of layers. The waves that propagate in the plane of the magnetic field are studied, and the area of parameters, for which the helicon waves propagate, is investigated. The existence of numerous narrow allowed bands is discovered. The magnetic field is shown to manage the electrodynamical properties and the location of bands.